2019
DOI: 10.1016/j.cities.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the stroke–built environment nexus in transitional cities: Conceptual framework, empirical evidence, and implications for proactive planning intervention

Abstract: Adverse lifestyle-associated health outcomes, and stroke in particular, have been aggravated in transitional countries under high-speed urbanisation. Against this backdrop, deciphering the nexus between built environments (BEs) and lifestyleassociated health outcomes is of importance for crafting proactive interventions. The existing literature on this topic, however, fails to sufficiently capture the multiplicity of health-related BEs and, in turn, the complexity of such a nexus, largely challenging the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Proximity to green spaces and high visit frequency is associated with a perceived mental well-being improvement and better physical health condition ( Romagosa, 2018 ; Houlden et al, 2019 ; Liu et al, 2019 ; Martin et al, 2020 ). People who are deprived of contact with nature or have difficult access to green areas are more at risk of depression and decreased functional ability, which in turn can lead to a significant deterioration in the quality of their life ( Whyte, 2001 ; Xie et al, 2019 ). That is why it seems essential for green areas in the urban agglomeration to be safe, available, and accessible to everyone, as for many people spending time in the park is the only possibility of close contact with nature in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Proximity to green spaces and high visit frequency is associated with a perceived mental well-being improvement and better physical health condition ( Romagosa, 2018 ; Houlden et al, 2019 ; Liu et al, 2019 ; Martin et al, 2020 ). People who are deprived of contact with nature or have difficult access to green areas are more at risk of depression and decreased functional ability, which in turn can lead to a significant deterioration in the quality of their life ( Whyte, 2001 ; Xie et al, 2019 ). That is why it seems essential for green areas in the urban agglomeration to be safe, available, and accessible to everyone, as for many people spending time in the park is the only possibility of close contact with nature in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two large-scale studies in multiple European and Chinese cities evaluated the association between urban form elements such as land covers and mortality ratios, finding that dense urban environments with a lack of green land covers were associated with a higher mortality [75,76]. Additionally, a study conducted by Xie, et al [77] in Wuhan, China, found that population density and building density were positively associated with stroke risk and, in contrast, a negative correlation between abundance of public parks and stroke risk, regardless of urban density. Similarly, Cusack, et al [78] observed positive associations between mothers' exposure to green space and term birth weight, especially in high-density locations in Vancouver and Toronto, Canada.…”
Section: Health and Well-beingmentioning
confidence: 99%
“…In demand generation, patient location is stratified solely by population density, despite a significant impact of aging, smoking, and hypertension. The assumption stems from a statistical analysis by Xie et al (2019), 59 which shows that net population density and building density are positively associated with stroke risk. Because of the timedependent nature of stroke treatment, stroke patients are highpriority patients; therefore, there are no waiting times associated with EMS or hospitals.…”
Section: Parameter Estimationmentioning
confidence: 99%